PENCATATAN DAN PERSAKSIAN TRANSAKSI HUTANG-PIUTANG: (Studi Perbandingan Tafsīr Al-Marāghī dan Tafsīr Al-Miṣbāḥ) (At-Tibyan, 2023)
This research was motivated by the emergence of differences in understanding regarding the interpretation of the QS. Al-Baqarah [2]: 282-283 or known by scholars as verse al-mudayānah (verses about debts). This issue has many opinions among interpretive scholars both regarding the recording order and the issue of testimony. To gain a deeper understanding, it is necessary to study this issue, so that we can find out what the position of authentic evidence and the criteria for witnesses are according to the interpreters. This research uses library research as a basic scientific perspective on the science of interpretation. The approach used in this research is the muqāran (comparative) approach. The results of this research state that there are three management concepts (procedures) for accounts receivable in QS. Al-Baqarah [2]: 282-283 according to Tafsīr Al-Marāghī and Tafsīr Al-Miṣbāḥ. First, record debts, whether large or small amounts. Second, present two male witnesses, or if there are not two men, one man and two women can be present. Third, provide collateral. According to Al-Marāghī, the legal status of debt recording is mandatory. This is based on the command in QS. Al-Baqarah [2]: 282 which requires writing down debts, as well as several benefits of writing down debts. According to him, debt recording aims to protect the rights of property owners, as well as avoid disputes that might arise in the future. Meanwhile, according to Quraish Shihab, the order to write down debts is understood by many scholars as a recommendation, not an obligation, because the order is difficult to carry out. If this command were mandatory, it would be very difficult for Muslims to implement because writing skills were very rare at that time